Efficacy of posterior reduction and internal fixation for the treatment of atlantoaxial dislocation in complex craniovertebral junction region malformation: preliminary observation - Gui⁃jun JIA; Hong⁃ming JI; Gang⁃li ZHANG; Yan ZHANG; Chang⁃chen HU; Jin⁃rui REN; Xiao⁃peng YAN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2012)
Objective To explore the clinical effect of posterior reduction and screw⁃rod (plate) internal fixation technique for the treatment of atlantoaxial dislocation in complex craniovertebral junction region malformation. Methods Clinical data of 18 patients suffered from atlantoaxial dislocation with complex craniovertebral junction region malformation were analysed retrospectively, including 15 cases of congenital atlantoaxial dislocation, 1 case with aggravated symptoms of cervico ⁃ occipital unstability after anterior odontoid process grinding, 2 cases with trauma ⁃ induced dislocation. All patients underwent posterior decompressive reduction and screw ⁃ rod internal fixation. During surgical procedure, senory evoked potential (SEP) and electromyography (EMG) monitorings were used. Japanese Orthopaedic Association (JOA) score and imaging were used to evaluate the surgical effect. Results Postoperative imaging examination showed that fixed system and atlantoaxial reduction were good in 16 cases and bad in 1 cases. The bony fusion was good in 16 cases and bad in 1 case. The patients' clinical symptoms were improved to different degree, but one patient suddenly occurred respiratory arrest and died. Patients were followed up for 3 to 28 months (mean 6.62 months). After operation the average JOA score was 11.62 ± 3.23, while before operation it was 7.51 ± 3.82. The difference was significant (t = ⁃ 5.476, P = 0.004). Conclusion Posterior decompressed reduction and screw ⁃ rod (plate) internal fixation for atlantoaxial dislocation with complex craniovertebral junction region malformation is save and effective. It will be widely used in the future.